Comparison of various cell disruption techniques on cadmium and zinc treated scenedesmus rotundus. - S. SUBHASHINI,; SARADA. D.V.L,; MALAVIKA VIJAY,; KAMINI. C, (International Journal of Pharma and Bio Sciences, 2018)
Scenedesmus rotundus was isolated from metal contaminated petroleum industrial effluents and was subjected to elevated levels of cadmium and zinc amended in Bold’s basal media. The growth was studied at a regular interval of two days to check the survival of the algae. The EC50 was calculated as 0.04 mM for Cd and 0.2 mM for Zn. Further effects of EC50 on growth, chlorophyll content and protein concentration was studied and they showed a reduction in cell count, chlorophyll content and an increase in membrane protein. To extract the total protein, the cells were processed for disruption. The metal treated cells were observed to be harder compared to the control attaining a rigid condition and the breakage was difficult. Henceforth various cell disruption techniques were studied to find the best suited method to obtain maximum yield of protein. In the current study various methods like Homogenization, sonication, manual grinding, salting out, TCA-Acetone and TCA-NaOH were studied among which TCA-Acetone was found to give a maximum yield of protein.